187k views
5 votes
Which rule is a recursive rule for the sequence 1,-6,36, -216

Which rule is a recursive rule for the sequence 1,-6,36, -216-example-1
User Nisal Edu
by
4.6k points

2 Answers

3 votes

Answer: 1*6°=6

1*(-6)^1=-6

1*(-6)^2=36

1*(-6)^3=-216

User Chirag Parmar
by
5.2k points
7 votes

Answer:

3rd option

Explanation:

There is a common ratio between consecutive terms , that is

r = - 6 ÷ 1 = 36 ÷ - 6 = - 216 ÷ 36 = - 6

To obtain a term in the sequence multiply the previous term by - 6

Then the recursive rule is


a_(n) = - 6 .
a_(n-1)

User Iamkaan
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.